Effectiveness of Board Governance at the Sydney Harbour Federation Trust : Sydney Harbour Federation Trust - Australian National Audit Office; Sydney Harbour Federation Trust (Barton, ACT : Australian National Audit Office, 2019)
The Sydney Harbour Federation Trust (SHFT) has a governing board and was established in September 2001 as a corporate Commonwealth entity under the Sydney Harbour Trust Act 2001 (SHFT Act) to conserve and preserve land in the Sydney Harbour region for the benefit of present and future generations of Australians. This includes land at Chowder Bay, Cockatoo Island, Georges Heights, Macquarie Lightstation, Marine Biological Station, Middle Head, North Head, Sub Base Platypus, and Woolwich. The audit examined the period July 2016 until March 2019.
"Auditor-General Report No.37 of 2018-19" --Cover.
Includes bibliographical references.
Also available online. Address as at 15/07/2019
Keywords: Sydney Harbour Federation Trust; Cultural property -- Protection -- New South Wales -- Sydney; Harbors -- New South Wales -- Sydney -- History; Historic preservation -- New South Wales -- Sydney Harbour; Sydney Harbour Region (N.S.W.); Australian